Cation exchange resin-induced hydrolysis for improving biodegradability of waste activated sludge: Characterization of dissolved organic matters and microbial community. (April 2020) - Pang, Heliang; Chen, Yiwen; He, Junguo; Guo, Dabin; Pan, Xinlei; Ma, Yingqun; Qu, Fangshu; Nan, Jun
Graphical abstract: Highlights: Cation exchange resin (CER)-mediated cation removal induced sludge disintegration. Spectral analysis was used to identify compositions and characterizations of DOMs. Protein, carbohydrate and other organic were main contributors for VFAs production. More than 85.2% of DOMs were easily biodegradable after CER-induced hydrolysis. Modified microbial community was responsible for DOMs characterizations. Abstract: This study reported an efficient and green approach towards facilitating hydrolysis of waste activated sludge (WAS) using cation exchange resin (CER) as a recyclable additive. Through CER-mediated removal of multivalent cations, WAS flocs were disintegrated into small particles with extracellular polymeric substance (EPS) solubilization. At CER dosage of 1.75 g/g SS, SCOD increased to 2579 mg/L (SCOD/TCOD = 15.9%) after 8-h hydrolysis. Afterwards, CER displayed further sludge hydrolysis performance lasting 2 days, i.e. SCOD/TCOD = 34.2%. Meanwhile, proteins, carbohydrates and other organics in dissolved organic matters (DOMs) were major contributors for volatile fatty acids (VFAs) accumulation, with composition percentage: VFAs (58.9%) > proteins (21.8%) > other organics (8.8%) > humic acids (5.9%) > carbohydrates (4.4%). The biodegradable tryptophan-like and tyrosine-like proteins were major proteins, while other organics included amino acids, aliphatic and metabolic intermediates. More than 85.2% of DOMs were easily biodegradable. Moreover, CER-induced hydrolysis modified microbial community structure through inhibiting VFAs-utilizing microbes, while hydrolytic-acidogenic bacteria were enriched, responsible for DOMs biodegradation.